Glucocorticoid therapy in patients with cerebral amyloid angiopathy-related inflammation: how useful are they? - Picón-Jaimes, Yelson A. (2022)
Objective. The objective of this review is to analyze the most recent evidence on the usefulness of glucocorticoids in patients with Inflammation Related to Cerebral Amyloid Angiopathy (IrCAA). Methods. Systematic review. A bibliographic search was carried out in the search engines and databases PubMed, ScienceDirect, Embase, EBSCO and MEDLINE databases, including any article related to the evaluation of the usefulness, efficacy or safety of glucocorticoids on inflammation of the cerebral amyloid angiopathy, would be included, giving priority to original studies and systematic reviews and meta-analyses. Results. It was found that the current evidence on its use is limited, deriving mainly from case reports, case series and retrospective studies. However, it seems that these agents cause a favorable response with partial resolution of the neurological manifestations immediately and/or progressively in the medium and long term, as well as abnormal imaging changes, given by vasogenic edema and cortical and subcortical microbleeds. although the improvement of the latter is not very marked. Conclusion. Current evidence on the use of glucocorticoids and their impact on clinical and neuroimaging outcomes is limited.